Development of strategies to facilitate the referral system of high-risk pregnant women between public sections in Bojanala District, North West, South Africa - Rasekele, Mapula Nelly (My University, 2022)
Background: The referral system is an essential component of the health system. The system meant to complement the Primary Health Care (PHC) principle of treating patients close to their homes at the lowest level of care with the needed expertise. Aim of the study: The aim of the study is to develop the strategies that will facilitate the referral system of high-risk pregnant women in between public sectors in the Bojanala district, North West Province, South Africa. Objectives of the study: To explore the referral system of high-risk pregnant women between public sectors within the Bojanala District, North West Province, South Africa. To develop strategies that will facilitate the referral system of high risk pregnant women in the Bojanala District, North West Province, South Africa. Methods: The researcher first obtained permission from the University of Limpopo Turfloop Research Ethics Committee (TREC), and further requested permission from the North West Department of Health, Bojanala District to conduct the study and was granted the permission. Qualitative, exploratory and descriptive designs were used to explore the referral system of high-risk pregnant women and to describe the strategies to facilitate the referral system of high-risk pregnant women in between public sectors in the Bojanala District, North West, South Africa. Non-Probability Purposive sampling method was used to select the midwives and obstetricians to participate in the study until data saturation was reached. Data were collected through one-on-one interviews using semi structured Interview Guide. The data were analysed using Tesch‘s eight steps of data analysis. Results: The results of this study revealed that the participants are knowledgeable about the referral system though they are many challenges that they encounter when managing high-risk women and having to refer them. They are aware of the current state of referral system and made their own suggestions on how to improve the referral system. Recommendations: Recommendations were made to facilitate the referral system of high-risk pregnant women in the North West Province, Bojanala District. The Department of Health must prioritise the provision of human and material resources to the district in order to achieve a better referral system and reducing the maternal and neonatal mortality as one of the millennium developmental goals. Conclusion: The referral system of high-risk pregnant women in the Bojanala District still has some challenges that need the intervention of the North West Department of Health to provide enough material and human resources to the Maternity Section in order to improve current status and to have an effective referral system
Thesis (M. (Nursing)) -- University of Limpopo, 2022
Keywords: Development; Referral System; High-Risk Pregnancy; Strategies; Women and Public Sectors.; Medical referral; Pregnancy -- Complications; Pregnant women -- South Africa -- North West; Hospitals -- Maternity services; Primary health care -- South Africa -- North West